Frames of variation in an economy for life - Herrera Torres, Hugo Amador (2021)
The objective of the paper is to define the limits that delineate the frame of variation of the economic process, taking into account the proposal of an economy for life of Hinkelammert and Mora. The method of analysis comprises two steps: 1) characterization of the reproductive rationality and the means-end rationality, which are the fundamental rationalities that make up the economic process in an economy for life; and 2) identification of the restrictions that reproductive rationality imposes on the means-end rationality. The results indicate, using a simple scheme with two producing subjects, that the frame of variation of the economic process has, at least, four limits. The upper limit is determined by nature, the lateral limits refer to the borders of existence of the producing subjects, who develop their activities inserted in a system of the social division of labor, so their actions depend, consequently, on the productive dynamics of others. The system considers two basic operating criteria, where one is in function of other. The first focuses on full employment for producers. The second refers to the fact that the technological innovation contained in the factors of production must be adjusted to full employment. The permanence of the producing subjects in the system guarantees that they meet the needs that allow reproducing the conditions that make their life possible. This guarantee traces to the lower limit, which indicates the minimum satisfaction of needs. The limits are covered of complexity, they can only represent approximations and their estimation incorporates qualitative and quantitative aspects.